Involvement of the CD95 (APO-1/Fas) receptor and ligand in liver damage - Galle, Peter R.; Hofmann, Walter J.; Walczak, Henning; Schaller, Heinz; Otto, Gerd; Stremmel, Wolfgang; Krammer, Peter H.; Runkel, Laura Ann (Journal of experimental medicine, 1995)
Apoptosis occurs in the normal liver and in various forms of liver disease. The CD95 (APO-1/Fas) (CD95) receptor mediates apoptosis, and liver cells in animal models are acutely sensitive to apoptosis initiated by this receptor. We have used primary human hepatocytes as a model system to investigate CD95-mediated apoptotic liver damage. Treatment of fresh human hepatocytes with low concentrations of agonistic antibodies against CD95 resulted in apoptosis of > 95% of the cultured liver cells within 4 and 7.5 h. Immunohistology of a panel of explanted liver tissues revealed that hepatocytes in normal livers (n = 5) and in alcoholic cirrhosis (n = 13) expressed low constitutive levels of CD95. CD95 receptor expression was highly elevated in hepatocytes in hepatitis B virus-related cirrhosis (n = 9) and in acute liver failure (n = 8). By in situ hybridization CD95 ligand messenger RNA expression was absent in normal liver but detected at high levels in livers with ongoing liver damage. In cases of hepatitis B virus-related cirrhosis and acute hepatic failure, ligand expression was found primarily in areas with lymphocytic infiltration. In contrast, in patients with alcoholic liver damage, high CD95 ligand messenger RNA expression was found in hepatocytes. These findings suggest that liver destruction in hepatitis B may primarily involve killing of hepatocytes by T lymphocytes using the CD95 receptor-ligand system. In alcoholic liver damage, death of hepatocytes might occur by fratricide and paracrine or autocrine mechanisms mediated by the hepatocytes themselves.